International news magazines coverage of 1995 Malaysian general election. - Hassan, Salleh; Tamam, Ezhar
This study proposed to find out how international news media covered the 1995 Malaysian national election in three ways 1) what are the issues covered in the news madia before and after the national election, 2) how the media view the election process and 3) the way the election outcomes are reported. Five popular international news magazines were selected for the study viz Times,The Economist,Newsweek,Asiaweek and Far Eastern Economic Review. All news articles on Malaysia that were published in these magazines from the months of April to May 1995 wree content analyzed. Two coders were employed to read and categorise the issues covered accordingly. The study found that the news magazines Asiaweek and Far Eastern Economic Review provided more coverage on the national election than other magazines with 8 and 22 articles respectively. The Time carried only one article during the period under study. On the issues covered before the election the major ones were:the economic achievement of the country,economic problems,credibility and ability of candidates; the chances and margins of victory for the ruling party;environmental issues and concerns the question of who benefited from the development programs of the country. Whereas,the coverage on the outcome of the election results centred on the implication of the election results on selected national leaders contribution of foreign workers in economic development and its implication;implication of election results on the opposition and economic achievements of the country. Three out the five news magazines reported that the stellar performance of the ruling party as a personal triumph of Dr. Mahathir and a vote for continuity in development. The election process in the country especially on the polling day was described by the international media as smooth and clean. Thus,it can be concluded that,the enws coverage about the national election by the international news madia was positive,evnthough they pointed out the lack of opportunity for the opposition to be covered by the local media.